2017
DOI: 10.9734/jamb/2017/32999
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Phytochemical Constituents and Antimicrobial Activities of Acalypha wilkesiana and Acalypha godseffiana Extracts

Abstract: Aim: The aim of the investigation was to evaluate and compare the phytoconstituents and antimicrobial activities of leaf extracts of two species of Acalypha (A. wilkesiana and A. godseffiana). Methodology: The methods employed include manual pulverization of the air-dried leaves and solvent (ethanol) percolation for 72 hrs. The crude extracts were kept in sterile Mc Cartney bottles and stored in the refrigerator 4±2°C. Thereafter, th ey were screened for phytochemical components. Moreover, they were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…However, experimental groups treated with aqueous extract of A. godseffiana leaf recorded reduced plasma AST and ALT activities when compared with H2O2 alone treated group. This is suggestive that A. godseffiana leaf extract possesses hepatoprotective and antioxidant properties which may be due to the presence of bioactive compounds such as flavonoids, proanthocyanidins, alkaloids, terpenoids, steroids and phenols [18,21,41,42]. This inference is supported by Asekunowo et al [43] who reported a positive relationship between phenolic content and antioxidant activity of extracts of A. godseffiana.…”
Section: Effects Of Acalypha Godseffiana Aqueous Leaf Extract On Antioxidant Enzymesmentioning
confidence: 71%
“…However, experimental groups treated with aqueous extract of A. godseffiana leaf recorded reduced plasma AST and ALT activities when compared with H2O2 alone treated group. This is suggestive that A. godseffiana leaf extract possesses hepatoprotective and antioxidant properties which may be due to the presence of bioactive compounds such as flavonoids, proanthocyanidins, alkaloids, terpenoids, steroids and phenols [18,21,41,42]. This inference is supported by Asekunowo et al [43] who reported a positive relationship between phenolic content and antioxidant activity of extracts of A. godseffiana.…”
Section: Effects Of Acalypha Godseffiana Aqueous Leaf Extract On Antioxidant Enzymesmentioning
confidence: 71%
“…Large numbers of herbal plants consider as an important medicinal plants and this importance revels the ability to cure different disease and infections as a result of its content from various secondary metabolites or bioactive compounds (31), and the most important bioactive compounds for Acalypha are flavonoids, phenols, quinones, alkaloids and tannins, which are concentrated in different plants parts from root to flowers and consider as an important character in taxonomical process between different taxa. (38) Acalypha Spp are known as a good resources of an important bioactive compounds with a distinctive roll in the environment and curing disease reveals from several studies in different species all over the world (1,2,11,23,25) while in Iraq there is no study for genus's chemical constitutes. This study was aimed to determine the distinctive features and phytochemical compound in aerial parts of new recorded species Acalypha australis in Iraq.…”
Section: Introductionmentioning
confidence: 99%